Are TREK Channels Temperature Sensors? - Rueda-Ruzafa, Lola; Herrera-Pérez, Salvador; Campos-Ríos, Ana; Lamas, J. A. (Frontiers in Cellular Neuroscience, 2021)
Internal human body normal temperature fluctuates between 36.5 and 37.5 ºC and it is generally measured in the oral cavity. Interestingly, most electrophysiological studies on the functioning of ion channels and their role in neuronal behavior are carried out at room temperature, which usually oscillates between 22 and 24 ºC, even when thermosensitive channels are studied. We very often forget that if the core of the body reached that temperature, the probability of death from cardiorespiratory arrest would be extremely high. Does this mean that we are studying ion channels in dying neurons? Thousands of electrophysiological experiments carried out at these low temperatures suggest that most neurons tolerate this aggression quite well, at least for the duration of the experiments. This also seems to happen with ion channels, although studies at different temperatures indicate large changes in both, neuron and channel behavior. It is known that many chemical, physical and therefore physiological processes, depend to a great extent on body temperature. Temperature clearly affects the kinetics of numerous events such as chemical reactions or conformational changes in proteins but, what if these proteins constitute ion channels and these channels are specifically designed to detect changes in temperature? In this review, we discuss the importance of the potassium channels of the TREK subfamily, belonging to the recently discovered family of two-pore domain channels, in the transduction of thermal sensitivity in different cell types.